Bilingualism and creativity: Benefits from cognitive inhibition and cognitive flexibility - Xia, Tiansheng; An, Yi; Guo, Jiayue (Frontiers in Psychology, 2022)
Bilingualism has been shown to be associated with creativity, but the mechanisms of this association are not very well understood. One possibility is that the skills that bilinguals use in switching back and forth between languages also promote the cognitive processes associated with creativity. We hypothesized that high-proficient Chinese-English bilinguals would show higher convergent and divergent thinking than low-proficient bilinguals, with the differences being mediated by cognitive inhibition and cognitive flexibility, respectively. Chinese university students (N = 54) were classified as high-proficient (n = 27) and low-proficient (n = 27) bilinguals based on their performance on the National English Test for College Students. As expected, group comparisons showed that the high-proficient group had higher scores on the Remote Associates Test (RAT, convergent thinking) and the Torrance Test of Creative Thinking (TTCT, divergent thinking). Also as expected, the association between bilingualism and convergent thinking was mediated by scores on a Stroop task (cognitive inhibition), and the association between bilingualism and divergent thinking was mediated by scores on a More-odd shifting task (cognitive flexibility). These findings suggest that bilingual learning can promote the development of different components of creativity through stronger cognitive inhibition and cognitive flexibility. The results provide empirical evidence for the relationship and mechanism between bilingual learning and creativity.